Lahan Pertanian Pangan Berkelanjutan (LP2B) dalam Penataan Ruang Wilayah: Tinjauan Literatur - Darmawansyah Darmawansyah; Bambang Sulistyo; Henry Farizal (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
The conversion of agricultural land to non-agricultural land continues to increase along with the pressures of urbanization, industrialization, and settlement expansion. This condition poses risks to food security, environmental sustainability, and farmer welfare. This article reviews literature based on 25 abstracts/research results on LP2B in Indonesia to map policy implementation patterns, the relationship between LP2B and regional spatial planning, inhibiting factors, and the direction of policy strengthening. The method used is a narrative review with thematic synthesis of normative legal studies, juridical-empirical, qualitative, mixed methods, and spatial-quantitative approaches. The results of the review indicate: (1) LP2B is highly dependent on the harmonization of spatial planning policies, especially RTRW/RDTR and licensing mechanisms based on KKPR-OSS; (2) many regions are still stuck at the land inventory-identification stage, not yet reaching the determination and operational protection through LP2B Regional Regulations; (3) dominant obstacles include regulatory asynchronous, weak law enforcement, minimal cross-agency coordination, limited data by name by address, suboptimal socialization, and conflicts of interest in non-agricultural development; (4) incentive-disincentive instruments have not been implemented consistently, although socially farmers tend to accept LP2B protection; and (5) quantitative evidence at the national level shows that LP2B policies have a positive effect on the percentage of rice fields, despite being suppressed by population density and real estate sector growth. This article emphasizes the need for an integrated spatial governance approach, strengthening regional institutions, and designing policies that are socially and environmentally just to ensure that LP2B is effective in maintaining regional food security.